THE CANADA-UNITED STATES OPEN BORDER PARADOX - Christian Leuprecht (The Journal of Intelligence, Conflict and Warfare)
On November 18th, 2024, Dr. Christian Leuprecht presented The Canada-United States Open Border Paradox for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were cross-border cooperation, the importance of Canada playing a proactive role in its border security, and emerging challenges with the changing nature of borders.